The Light of Knowledge : Literacy Activism and the Politics of Writing in South India - Cody, Francis, 1976- (Book collections on Project MUSE., 2013)
Cowinner of the Society for Linguistic Anthropology's Edward Sapir Book Prize Since the early 1990s hundreds of thousands of Tamil villagers in southern India have participated in literacy lessons and other events designed to transform them into active citizens with access to state power. These efforts are part of a movement known as the Arivoli Iyakkam (the Enlightenment Movement), one of the most successful mass literacy movements in recent history. This rich ethnographic account of highlights the paradoxes inherent in such movements that seek to emancipate people through literacy.